Genome Editing in Trees: From Multiple Repair Pathways to Long-Term Stability - Bewg, William Patrick; Ci, Dong; Tsai, Chung-Jui (Frontiers in Plant Science, 2018)
The CRISPR technology continues to diversify with a broadening array of applications that touch all kingdoms of life. The simplicity, versatility and species-independent nature of the CRISPR system offers researchers a previously unattainable level of precision and control over genomic modifications. Successful applications in forest, fruit and nut trees have demonstrated the efficacy of CRISPR technology at generating null mutations in the first generation. This eliminates the lengthy process of multigenerational crosses to obtain homozygous knockouts. The high degree of genome heterozygosity in outcrossing trees is both a challenge and an opportunity for genome editing: a challenge because sequence polymorphisms at the target site can render CRISPR editing ineffective; yet an opportunity because the power and specificity of CRISPR can be harnessed for allele-specific editing. Examination of CRISPR/Cas9-induced mutational profiles from published tree studies reveals the potential involvement of multiple DNA repair pathways, suggesting that the influence of sequence context at or near the target sites can define mutagenesis outcomes. For commercial production of elite trees that rely on vegetative propagation, available data suggest an excellent outlook for stable CRISPR-induced mutations and associated phenotypes over multiple clonal generations.